2023
DOI: 10.3390/ma16103641
|View full text |Cite
|
Sign up to set email alerts
|

Uniaxial Rotational Molding of Bio-Based Low-Density Polyethylene Filled with Black Tea Waste

Abstract: In this paper, the possibility of obtaining uniaxially rotomolded composite parts was discussed. The used matrix was bio-based low-density polyethylene (bioLDPE) filled with black tea waste (BTW) to prevent the thermooxidation of samples during processing. In rotational molding technology, the material is held at an elevated temperature in a molten state for a relatively long time, which can result in polymer oxidation. The Fourier transform infrared spectroscopy (FTIR) shows that adding 10 wt% of black tea wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…All publications are within the past 5 years. Natural fillers such as black tea, giant reed, wood, hemp and rice were amongst findings accompanied by the experimental work with recycled carbon fibres [ 30 , 31 , 32 , 33 , 34 , 67 ]. Abhilash et al [ 34 ] reported that the addition of risk husk improved the vibrational properties from an experimental modal analysis (EMA), alluding to suitability for automobile vibrating applications by up to 15 wt% addition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All publications are within the past 5 years. Natural fillers such as black tea, giant reed, wood, hemp and rice were amongst findings accompanied by the experimental work with recycled carbon fibres [ 30 , 31 , 32 , 33 , 34 , 67 ]. Abhilash et al [ 34 ] reported that the addition of risk husk improved the vibrational properties from an experimental modal analysis (EMA), alluding to suitability for automobile vibrating applications by up to 15 wt% addition.…”
Section: Resultsmentioning
confidence: 99%
“…Aniśko and Barczewski studied bio-based PE and black tea waste from a tea distribution company [ 67 ]. Black tea would otherwise have been removed to landfill.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the presence of CAT in the blend causes a sharp reduction in maximum elongation at break, decreasing to 27% at 1 wt% CAT and only 8% at 10 wt% CAT. The stiffness of the blend increases proportionally to the amount of CAT present, with a maximum increase in the tensile modulus of 37% at 10 wt% CAT with respect to neat LDPE [ 44 , 45 ]. Nevertheless, yield strength and strain are not improved, showing no change at 1 wt% CAT, and a 17% reduction at higher CAT content.…”
Section: Resultsmentioning
confidence: 99%